Titanate based ceramic dielectric materials - Saravanan, Ramachandran, 1964- (Materials research foundations ;, 2018)
The book presents research results concerning the electron density distribution in a number of doped barium titanate ceramic materials using experimental X-ray diffraction data, UV-visible spectrophotometry (UV-vis), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). The analysis of interatomic bonding and electron density distribution is important for predicting the properties of potentially important materials and has previously been lacking for the materials studied.